Trade openness, growth, income inequality and environment in developing and OECD countries - Idris, Jamilah (2015)
Trade openness can be very important for country’s development and economic growth. Much of the debates have focused on the role of trade openness on growth even though it can also be related to income inequality and environment. The objective of this study is to investigate the relationship between trade openness, economic growth, income inequality and environment in a global perspective covering 87 selected countries, which is comprises the Organisation for Economic Co-operation and Development (OECD) and developing countries for the period 1977 to 2011. The first objective is to determine the impact of trade openness on economic growth, while the second objective is to analyse the relationship between trade openness and income inequality, and the third objective is to determine the impact of trade openness on environment. This study employs the system Generalized Method of Moments (GMM), a method popularized by Arellano and Bond (1991), and Blundell and Bond (1998). Our result suggests that trade openness has positive impact on economic growth in all countries (87), OECD and developing countries. Although trade openness is important for growth stimulation, opening up new markets and exposing domestic firms to international practices, trade can create the necessary conditions for poverty alleviation. Our study found that trade openness has improved income inequality in developing countries which support the Heckscher Ohlin theory except for OECD countries. Finally, our results suggest that openness along with the other variable such as economic growth, foreign direct investment and manufacturing value added do have positive impact on CO2 emission. Comprehensive environmental policies, legislation, and the role of institutions are important in order to manage the CO2 emission problem. Policy makers should also put more thought on promoting growth through trade but also how the benefit from the growth is well distributed across the population while keeping the environment clean and healthy.